Liebenberg syndrome severity arises from variations in Pitx1 locus topology and proportion of ectopically transcribing cells - Olimpia Bompadre; Raquel Rouco; Fabrice Darbellay; Antonella Rauseo; Fanny Guerard-Millet; Claudia Gentile; Marie Kmita; Guillaume Andrey (Nature Communications)
Abstract Enhancer hijacking, a common cause of gene misregulation linked to disease, occurs when non-matching enhancers and promoters interact ectopically due to genetic alterations. While the concept of enhancer hijacking is well understood, the reasons behind the variation in phenotypic severity remain unexplored. In this work, we expand on the ectopic activation of the hindlimb-specific transcription factor Pitx1 by one of its own enhancers, Pen, in forelimb tissues that causes the Liebenberg syndrome. Using a series of inversions and relocations we show that reduction in Pitx1-Pen relative genomic positioning leads to increased proportions of Pitx1 forelimb-expressing cells and more severe phenotypical outcomes. We demonstrate in ectopically expressing cells that the Pitx1 locus assumes an active topology and that its promoter generates consistent transcription levels across different alleles. Finally, we show that changes in 3D chromatin structure and enhancer-promoter contacts are not the result of Pitx1 transcription.